OLYMPIC EDUCATION - Part 1 Theoretical and methodological principles of current Olympic education - Galan, Yaroslav; Perederiy, Vira; Beshlei, Оlga (LAP LAMBERT Academic Publishing, 2021)
The monograph studies historical, theoretical and methodological aspects of the development of Olympic education, its functioning and integration into the educational process. The authors analyse, generalise and characterize innovative forms of Olympic education. It provides a theoretical review of Olympic education which can be used in organizing educational activities for students, teachers and educators in general. The paper describes various aspects of patriotic education of the youth that draw on the principles and foundations of Olympic education, which allows to form national universal values.The monograph is recommended for use in the professional pedagogical or scientific activities by physical education teachers, graduate students, students or others whose research is aimed at studying the basic principles of Olympic education.
Keywords: Olympic education, sport